Flower arranging for every day and special occasions. ([Des Moines] Meredith Publications, 1957)
A guide to the many facets of floral arranging such as balance, proper container, and choice of flowers; includes rules and practices of the National Council of State Garden Clubs.
Keywords: Flower arrangement